CRACKING ACTIVITY OF PREPARED Y-ZEOLITE CATALYST USING CUMENE ON FLUIDIZED BED REACTOR - A.K. Mohammed, Abdul Halim; Ghassan Yousuf, Rawa; Khalifa Esgair, Karim (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
The catalytic activity of faujasite type NaY catalysts prepared from local clay (kaolin) with different Si/Al ratio was studied using cumene cracking as a model for catalytic cracking process in the temperature range of 450-525° C, weight hourly space velocity (WHSV) of 5-20 h1, particle size ≤75μm and atmospheric pressure. The catalytic activity was investigated using experimental laboratory plant scale of fluidized bed reactor. It was found that the cumene conversion increases with increasing temperature and decreasing WHSV. At 525° C and WHSV 5 h-1, the conversion was 42.36 and 35.43 mol% for catalyst with 3.54 Si/Al ratio and Catalyst with 5.75 Si/Al ratio, respectively, while at 450° C and at the same WHSV, the conversion was decreased to 29.15 and 21.86 mol% respectively, and the catalyst of 5.75 Si/Al ratio gave the higher cumene activity than the catalyst with 3.54 Si/Al ratio.